2015
DOI: 10.1186/s12888-015-0671-y
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression during pregnancy in Central America: a cross-sectional study among pregnant women in the developing country Nicaragua

Abstract: BackgroundAround the world, maternal psychopathology during pregnancy is associated with a range of negative consequences for mother and child. Nevertheless, in Central America the magnitude of this public health problem is still unknown. The objective of this first explorative study was to investigate the prevalence and severity of anxiety and depression during pregnancy in the Central American developing country Nicaragua, as well as the availability of mental health care and to compare with a developed coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 24 publications
1
40
1
4
Order By: Relevance
“…The PRIDE Study questionnaires in early (weeks [10][11][12] and late (week 34) pregnancy included the Hospital Anxiety Depression Scale (HADS), a 14-item self-completion screening scale to indicate the possible presence of symptoms of depression and anxiety. 19 The questionnaire consists of two subscales, one for symptoms of depression (HADS-D) and one for symptoms of anxiety (HADS-A), with a 4-point rating scale (0-3), adding up to a score range of 0-21 for each subscale.…”
Section: Hospital Anxiety Depression Scale (Hads)mentioning
confidence: 99%
See 1 more Smart Citation
“…The PRIDE Study questionnaires in early (weeks [10][11][12] and late (week 34) pregnancy included the Hospital Anxiety Depression Scale (HADS), a 14-item self-completion screening scale to indicate the possible presence of symptoms of depression and anxiety. 19 The questionnaire consists of two subscales, one for symptoms of depression (HADS-D) and one for symptoms of anxiety (HADS-A), with a 4-point rating scale (0-3), adding up to a score range of 0-21 for each subscale.…”
Section: Hospital Anxiety Depression Scale (Hads)mentioning
confidence: 99%
“…7,8 For the latter, one study reported a decrease from 11.0% to 8.5% over the course of pregnancy, 9 while another reported an increase from 7.4% in early pregnancy to 12.8% in middle, and 12.0% in late pregnancy. 8,11 Some reported an increase in anxiety, 12 while others reported a U-shaped pattern, 8,13 or a decrease over the course of pregnancy. 8 Prevalence rates of anxiety and changes over time during pregnancy have been studied less extensively compared with depression, with prevalence rates ranging from 15.0% to 36.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of anxiety have been estimated to affect 16% of pregnant women (first trimester) . Other studies have placed the estimate closer to 10% . There is evidence that symptoms of anxiety may be experienced by as many as 40% of women in developing nations .…”
Section: Introductionmentioning
confidence: 99%
“…11 Other studies have placed the estimate closer to 10%. 12 There is evidence that symptoms of anxiety may be experienced by as many as 40% of women in developing nations. 12 In one study, symptoms of anxiety appeared to decrease over the course of pregnancy (from the first to third trimesters 17.9% to 14.2%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation